Comparative proteomic analysis revealing the complex network associated with waterlogging stress in maize (Zea mays L.) seedling root cells. Issue 1 (3rd December 2014) - Yu, Feng; Han, Xuesong; Geng, Cunjuan; Zhao, Yanxin; Zhang, Zuxin; Qiu, Fazhan
<x xml:space="preserve">Abstract</x> Soil waterlogging is one of the major abiotic stresses affecting maize grain yields. To understand the molecular mechanisms underlying waterlogging tolerance in maize, the iTRAQ LC‐MS/MS technique was employed to map the proteomes of seedling root cells of the A3237 (tolerant inbred) and A3239 (sensitive inbred) lines under control and waterlogging conditions. Among the 3318 proteins identified, 211 were differentially abundant proteins (DAPs), of which 81 were specific to A3237 and 57 were specific to A3239. These DAPs were categorized into 11 groups that were closely related to the plant stress response, including metabolism, energy, transport, and disease/defense. In the waterlogged A3237 root cells, NADP‐malic enzyme, glutamate decarboxylase, coproporphyrinogen III oxidase, GSH S‐transferase, GSH dehydrogenase, and xyloglucan endotransglycosylase 6 were specifically accumulated to manage energy consumption, maintain pH levels, and minimize oxidative damage. The evaluations of five specific physiological parameters (alcohol dehydrogenase activity and GSH, malondialdehyde, adenosine 5'‐triphosphate, and nicotinamide adenine dinucleotide concentrations) were in agreement with the proteomic results. Moreover, based on the proteomic assay, eight representative genes encoding DAPs were selected for validation at the transcriptional level. qRT‐PCR revealed that the expression levels of these genes correlated with their observed protein abundance. These findings shed light on the complex mechanisms underlying waterlogging tolerance in maize. All MS data have been deposited into the ProteomeXchange with the identifier PXD001125 http://proteomecentral.proteomexchange.org/dataset/PXD001125.